Managing beyond the factory walls: Effects of four types of strategic integration on manufacturing plant performance - Swink, Morgan; Narasimhan, Ram; Wang, Cynthia (Journal of Operations Management, 2007)
AbstractIn this paper we focus on the integration of strategic objectives and process knowledge that a manufacturing factory collects from its external interfaces. Using data from a variety of manufacturing industries, this study examines four different types of strategic integration at the manufacturing plant level. We use a path analytic approach to simultaneously assess the contributions of the various types of integration to manufacturing‐based competitive capabilities and business level performance. In addition, we examine the intervening roles that manufacturing‐based competitive capabilities play in mediating the relationships between strategic integration and business performance. We find that each type of integration activity has unique benefits and detriments. These findings extend prior studies of manufacturing and supply chain integration by broadening the theory relating to strategic integration. The results also provide implications for manufacturing managers who seek to design integration policies and associated resource deployments.